Pro-health education in the fight against obesity and its complications among school-age children – 6-month program of cooperation with a child and parents - Kołpa, Małgorzata; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2018)
Introduction: The dynamic development of society affects the health of the population. We often address civilization-related diseases affecting increasingly younger people. The lack of both a balanced diet and physical activity leads to hypertension and obesity. These diseases have a number of serious consequences. The aim of the study was to demonstrate the influence of an educational programme on the arterial pressure and body weight status of children between 10 and 12 years of age. Material and methods: The study (education program) involved 60 primary school pupils in grades 4-6, including 40 boys and 20 girls whose BMI and arterial blood pressure values differed, higher from the standard norms. Anthropometric measurements were made, i.e., height, body weight, blood pressure and blood biochemical tests. Then, the pupils were taken care of by a dietician and a trainer. Results: The problem is the small number of fruits and vegetables in the children’s diet, which is far below the recommended standards. In the study group, nearly 12% of the children had elevated TSH levels. Physical activity of the participants was low and was mostly limited to compulsory physical education lessons. According to the surveys carried out the girls were physically active much less frequently than the boys. Conclusions: The increase in the BMI index results in increased systolic pressure in children. An increase in TSH increases the value of diastolic pressure in 10- to 12-year-olds. Children eat too few fruits and vegetables per week compared to the established standards. The implementation of an educational programme in nutrition and physical activity affects the reduction of BMI in children with excess body weight.